Strength of Ice under Multiaxial Loading. - Lankford,James; Francis,Philip H. (1975)
Strength tests were carried out using hollow, cylindrical specimens of polycrystalline ice, subject to combined axial compression, internal/external pressure. A portion of the failure envelope in principal stress space was mapped out and compared with data of other workers. The results of all available multiaxial tests can fit by a modified Paul first order criterion.